2010
DOI: 10.1039/c0an00232a
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of anti-Sudan red monoclonal antibody and development of an indirect competitive enzyme-linked immunosorbent assay for detection of Sudan red in chilli jam and chilli oil

Abstract: Sudan dyes are banned to be used in food additives because of the carcinogenicity of their metabolites. A rapid and sensitive indirect competitive enzyme-linked immunosorbent assay (ELISA) was developed to detect the residues of Sudan dyes. Novel immunogen and coating antigen were synthesized via glutaraldehyde linking. The hapten-bovine serum albumin (BSA) was applied as immunogen and the hapten-ovalbumin (OVA) was served as coating antigen. The monoclonal antibody obtained showed high sensitivity to Sudan I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 15 publications
(12 reference statements)
4
25
1
Order By: Relevance
“…These substitutes influenced the recognition of the antibodies to the three dyes. Still, the crossreactivities for Sudan 2 and Sudan 4 were higher than the previous reported antibodies (Anfossi et al, 2009;Han et al, 2007;Ju et al, 2008;Wang et al, 2009;Xu, Wei et al 2010;Xu, Zhang et al 2010).…”
Section: Elisa Methods Optimizationcontrasting
confidence: 79%
See 2 more Smart Citations
“…These substitutes influenced the recognition of the antibodies to the three dyes. Still, the crossreactivities for Sudan 2 and Sudan 4 were higher than the previous reported antibodies (Anfossi et al, 2009;Han et al, 2007;Ju et al, 2008;Wang et al, 2009;Xu, Wei et al 2010;Xu, Zhang et al 2010).…”
Section: Elisa Methods Optimizationcontrasting
confidence: 79%
“…Therefore, among the four combinations the best combination was combination 2 (PR-N-OA combining antibody R4) with crossreactivities in the range of 36%e108% and these results were better than the previous reports (Anfossi et al, 2009;Han et al, 2007;Ju et al, 2008;Wang et al, 2009;Xu, Wei et al 2010;Xu, Zhang et al 2010). The worst combination was combination 4 (PR-C-OA combining antibody R4).…”
Section: Elisa Methods Optimizationmentioning
confidence: 45%
See 1 more Smart Citation
“…From the curve in Fig. 4, we can calculate that the noise signal originated from concentration variation was 0.29 ng ml −1 , and the LOD was~1 ng ml −1 (3 × noise signal) which was the same as the LOD in well-plate assay (SI, Figure S3) or even lower than many established methods such as in well plate ELISA (1.7 ng ml −1 ) (Xu et al 2010) and HPLC (1.8 μg kg −1 , equivalent to 9 ng ml −1 ) (Long et al 2011). This LOD is repeatable with the same level in VAMI.…”
Section: Accelerating the Immunoassaymentioning
confidence: 98%
“…In recent years, it was demonstrated that immunosorbent assays [18][19][20][21] as well as electrochemical sensors based on voltammetric readout [22][23][24] can be applied for this analytical problem. Additionally, the applicability of nuclear magnetic resonance (NMR) spectroscopy in combination with chemometric methods was presented [25,26].…”
Section: Introductionmentioning
confidence: 99%